2014
DOI: 10.1111/pai.12274
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune disease comorbidities in patients with atopic dermatitis: a nationwide case–control study in Taiwan

Abstract: Our study confirmed the association between AD and LE. Early survey for LE in juvenile patients with AD is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 53 publications
3
68
0
1
Order By: Relevance
“…As T and B helper cells are involved in the pathogenesis of both atopy and autoimmune disease, a positive association is speculated [46]. Many common immune pathways underlying autoimmune disease and atopy, featuring Th2, Th17, Treg, and Toll-like receptors (TLRs) have been the subject of several recent reports [1720, 47]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As T and B helper cells are involved in the pathogenesis of both atopy and autoimmune disease, a positive association is speculated [46]. Many common immune pathways underlying autoimmune disease and atopy, featuring Th2, Th17, Treg, and Toll-like receptors (TLRs) have been the subject of several recent reports [1720, 47]. …”
Section: Discussionmentioning
confidence: 99%
“…Some indications for the plausibility of underlying similarities are the rise in prevalence of both disease groups in the 20th century [15]. Previous researches showed epidemiological correlations and a substantial pathophysiological relationship between atopy and SLE [2, 16, 17]. Furthermore, many recent discoveries have challenged that there is no connection between atopic diseases and autoimmune disorders and even suggested that autoimmune and atopic diseases may be risk factors for each other, contributing to the high prevalence of both diseases [2, 13, 16, 18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in one study, maternal rheumatoid arthritis/ankylosing spondylitis was shown to be associated with both asthma and hay fever in her children, although they did not report any association with AD . No positive or negative associations were found with endocrine autoimmune disease despite an inconsistently reported inverse association between type 1 diabetes and AD …”
Section: Discussionmentioning
confidence: 95%
“…3,5 Atopic dermatitis has been associated with a wide variety of autoimmune conditions including dermatologic diseases including vitiligo, 6,7 alopecia areata [6][7][8][9] and chronic urticaria, 6 but also gastrointestinal autoimmune diseases such as ulcerative colitis, 6,[10][11][12][13] Crohn's disease, 6,10,[12][13][14] and coeliac disease 6,15,16 and rheumatologic autoimmune diseases such as systemic lupus erythematosus. 6,17 Mixed or non-significant associations have been reported with diabetes mellitus type 1, 10,17,18 rheumatoid arthritis 10,[19][20][21] and ankylosing spondylitis. 19,20 The observed associations may be explained in part by surveillance bias in registerbased studies, but overlap in genetic risk loci has indeed been identified suggesting that AD and autoimmune diseases may have shared origin.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Lung‐chi and Chian‐Yaw et al . adopted the National Health Insurance Research Database (NHIRD) from the National Health Insurance (NHI) program, a public healthcare system enrolled more than 99% population in Taiwan, to examine the association of AD and several autoimmune diseases.…”
Section: Autoimmune Disease Comorbidities In Patients With Atopic Dermentioning
confidence: 99%